The Role of Leaders in Managing the Coretax Application Information System Gap - Martinus Sony Erstiawan (CONTABILITA : Journal of Accounting and Finance, 2025)
This study aims to analyze the information gap in the implementation of the Coretax system, a strategic project of the Indonesian government for tax modernization. Although Coretax was designed to improve efficiency and accountability, there is a discrepancy between positive claims from the bureaucracy and ongoing complaints from taxpayers. This gap indicates a dysfunction in the internal reporting system exacerbated by a "Asal Bapak Senang" culture, which hinders accountability. This study used a qualitative approach with content analysis of relevant online news from May to September 2025. Data were systematically analyzed through coding and categorization to identify patterns, motives, and relationships between actors. The results show that the Coretax problem is not merely technical but also stems from bureaucratic management. This study found the crucial role of transformational leadership in addressing the information gap. Minister of Finance Purbaya, through proactive actions such as calling the Kring Pajak service, successfully cut off dishonest reporting channels and obtained an accurate picture of conditions on the ground. This step not only practically addressed the problem but also acted as a strategy to restore public trust. The conclusion is that the success of technology projects in the public sector is highly dependent on leadership that dares to fight against dysfunctional bureaucratic culture so that the accountability and effectiveness of the Coretax application can be trusted again by the public, especially by taxpayers.